Numerical study on thermal enhancement in magnetohydrodynamic micropolar liquid subjected to motile gyrotactic microorganisms movement and Soret and dufour effects - Abdelatif Salmi; Hadi Ali Madkhali; Maryam Haneef; Sayer Obaid Alharbi; M.Y. Malik (Case Studies in Thermal Engineering, 2022)
Motile gyrotactic organism activity in micropolar fluid subjected to simultaneous heat and mass transfer in the presence of thermal diffusion and diffusion thermo effects is modeled. The base fluid is taken as kerosene oil. The immersion of nano-sized particles of Cu−TiO2 kerosene oil makes its rheological characteristics of micropolar fluid because nano-sized particles serve as micro-structures. In this case couple stress, vortex and spin gradient viscosities become significant and simultaneously linear and angular momenta become equally remarkable. So, micropolar theory is the best to model the immersion of nano-structures in the fluid. Similarity variables are used to transform the problems into their dimensionless forms. The mathematical models are solved numerically by applying the finite element method (FEM). The results are validated and numerical experiments are performed to analyze the key parameters of the unknown field variables. In order to analyze the impact of physical parameters on field variables, numerous simulations are performed. The micro-rotation of microparticles and nanoparticles due to fluid deformation motivates fluids particles to rotate faster. Therefore, linear motion is observed to be increased for higher values of vortex viscosity. The curvature parameter has significantly impacted the linear motion of the fluid particles. The impact of the curvature parameter on the movement of nanofluid is lesser than the impact of the curvature parameter on the motion of hybrid nanoparticles. Concentration gradient supports the diffusion of heat in the fluid regime and numerical experiments with variation of Dufour (that measures the effects of concentration gradient on heat diffusion) have shown that concentration gradient is more effective in the case of hybrid nanofluid relative to the mono nanofluid. The angular motion of fluid particles increases when vortex viscosity is increased. Numerical simulations have predicted that the angular motion of particles of hybrid nanofluid has a lesser angular speed than that of the angular motion of particles of mono nanofluid. The Soret number determines the impact of temperature gradient on the diffusion of solute in the fluid. Simulations for various values of Soret number have predicted that the impact of temperature gradient on the diffusion of solute in hybrid nanofluid is stronger than the impact of temperature gradient on the diffusion of solute in mono nanofluid.